HUBUNGAN KINERJA KEUANGAN BANK SYARIAH, ORIENTASI PASAR, ORIENTASI PEMBELAJARAN, DAN MODAL RELASIONAL - Moh Khoiruddin; Andhi Wijayanto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This study aims to determine the relationship of the financial performance of Islamic banks, market orientation, learning orientation, and relational capital. By knowing the kind of relationship would be beneficial for improving the financial performance of Islamic banks which have distinctive core business. The population in this study was the manager of Islamic banks in the province of Central Java. With purposive random sampling, 119 samples are obtained. SEM analysis results show the effect of learning orientation on market orientation, market orientation effect on relational capital, relational capital effects on the financial performance, the effect of learning orientation on financial performance, the effect of market orientation on financial performance is significant. Goodness of Fit value of the model is quite satisfactory.